Take a Stand!–a multi-component intervention aimed at reducing sitting time among office workers–a cluster randomized trial. (19th April 2016) - Danquah, IH; Kloster, S; Holtermann, A; Aadahl, M; Bauman, A; Ersbøll, AK; Tolstrup, JS
Abstract: Background: Prolonged sitting time has been associated with adverse health outcomes. Interventions at work may contribute to reduced sitting. The objective was to test if a multicomponent work-based intervention can reduce sitting time and the number of prolonged sitting periods (> 30 min), increase the number of sit-to-stand transitions and decrease waist circumference and body fat percentage among office workers. Primary outcomes were: change in sitting time, prolonged sitting periods and sit-to-stand transitions at follow-up 1 month later. Methods: At four workplaces, 19 offices (317 workers in total) were cluster randomized for intervention or control. The intervention included the appointment of local ambassadors, management support, environmental changes, a lecture and a workshop. Sitting time was measured using an ActiGraph GT3X+ fixed on the thigh. Data were processed using Acti4 software providing data on time spent sitting, standing and doing other activities. Control participants were instructed to behave as usual. Follow-up measurements were obtained after 1 and 3 months. Results: At 1 and 3 months, total sitting time was 71 ( P < 0.001) and 48 min ( P < 0.001) lower per 8-h workday in the intervention group compared with the control group. At 1 month, the number of prolonged sitting periods was lower (-0.79/8-h workday, P < 0.001) and sit-to-stand transitions were higher (+14%/sitting hour, P = 0.001) in the intervention compared with the control group. After 3 months, trends persisted. The body fat percentage was lower by 0.61 percentage points ( P = 0.011) in the intervention group compared with the control group after 3 months. Conclusions: The multicomponent workplace-based intervention was effective in reducing sitting time, prolonged sitting periods and body fat percentage, and in increasing the number of sit-to-stand transitions.